Restaurant Service System During Special Events Based On International Experience At Lanta Nice Beach Resort, Thailand - Nuranissa, Dinda Widy; Rohim, Abdul; Kartini, Raden Asri; Adrial, Adrial (Community Services and Social Work Bulletin, 2025)
This study examines the strategic role of restaurant servers in enhancing guest experience and operational success during major festive events, specifically Christmas and New Year’s celebrations at Lanta Nice Beach Resort, Thailand. Based on insights from an international internship program, the paper underscores how restaurant staff perform multiple roles that extend beyond food delivery, including creating an inviting atmosphere, facilitating communication between guests and management, and serving as cultural intermediaries in a multicultural hospitality setting. The analysis identifies core responsibilities of servers, highlights service challenges during peak demand, and emphasizes the competencies required to accommodate diverse international guests. Findings reveal that effective restaurant service relies on a combination of technical proficiency, interpersonal communication, cultural sensitivity, and stress management under time constraints. These results contribute to a deeper understanding of frontline hospitality roles in tourism studies and offer practical implications for workforce training, event management, and service quality improvement in resort settings.